ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INDIVIDU PENGGUNA SISTEM INFORMASI DENGAN MENGGUNAKAN MODEL DELONE DAN MCLEAN (Studi Empiris pada Pengguna Aplikasi Sistem Informasi Akuntansi di BNI) - Nurul Laksmiyati; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
This research discuss about factors that can effect individual performance of information system’s user based on DeLone and McLean’s Model. This model uses six factors that can measure an information system’s success, those are information system quality, information quality, intensity of system information use, end user satisfaction, individual impact, and organizational impact from information system.Independent variables used in this research are information system quality, information quality, service quality, and facilitating condition. Then, the dependent variable is individual performance of information system’s user. This research also uses intervening variable, that is information system’s user satisfaction. This research uses survey method by questionnaire in collecting the data. The questionnaires are given to BNI employees in Product Management and Retail Department with the usable response rate is 91%. Afterwards, the data gained is analysed using PLS (Partial Least Square).The results of this research are information system quality, information quality, service quality, and facilitating condition that can effect individual performance of information system’s user through user satisfaction.